Profitabilitas dalam Memediasi Hubungan Leverage Terhadap Penghindaran Pajak - Malinda, Cut Mandha; Pradana, Ayub Wijayati Sapta (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p09, 2022)
This study aims to examine the effect of leverage on tax avoidance with profitability as a mediating variable. The research was conducted on manufacturing sector companies that have been listed on the Indonesia Stock Exchange for the period 2016 – 2020. The sampling method used was purposive sampling and resulted in 57 sample companies using Partial Least Square (PLS) data analysis techniques. The results showed that leverage had a negative effect on profitability. Leverage has a positive effect on tax avoidance. Profitability has a negative effect on tax avoidance and is unable to mediate the relationship between leverage and tax avoidance.               Keywords: Leverage; Profitability; Tax Avoidance.